Numerical Models For Boundary-Layer Analysis On Rough Surfaces - Saeed, Farooq (2004)
The paper presents a brief overview of the two most commonly used approaches, namely the equivalent sand-grain approach and the discrete-element approach, used to study boundary-layer characteristics of a rough surface. The salient features as well as some of the recent improvements and the limitations of these approaches are highlighted. Some results are presented at the end to show a comparison with known experimental data